Employment Change and Business Prospects in Serbia - Ognjenovic, Kosovka Đ; Branković, Aleksandra (Industrija, 2013)
The aim of this article is to examine whether some previous knowledge about business prospects affects companies’ decisions about new employment in Serbia. In order to investigate this assumption a set of firm level data for 2012 is used. Following the theoretical approach that put an employer in a position to make various decisions about employment within the company, the trichotomous logit model is employed for the estimation of outcomes of possible companies’ decisions with respect to a set of independent variables. We find that the level of employment in the year that precedes companies’ decisions and relative changes in the number of employees in two successive years, as well as age and size of the company to some extent, affect companies’ decisions about new employment. The most important finding of our research is that the companies that experienced fluctuations in the number of employees and upgraded their business opportunities in the previous period hesitate to make decisions on the engagement of new workers, whereas those companies that lost some business opportunities rather decide to downsize the total number of employees.